Assessment of dieback pathogens of apple trees to be removed and the detection of diplodia seriata on chipped apple wood - Jacobs, Vernon Guy (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.